Executives ecocentric perspective in framing corporate environmentalism - Behjati, Saeed (2014)
Natural hazards and the vulnerability of the affected people due to their outcomes, in Iran, have prompted the notion of corporate environmentalism. Debates on environmentalism had caused the reason for corporate environment responsiveness yet to be part of a core business strategy despite extensive awareness and societal and institutional isomorphism. Due to the exploratory nature of social epistemology, this research employed the qualitative approach and multiple case studies to explore the nature of the construction of corporate environmentalism. The voices of corporate executives offered a glimpse of their commitment and the factors they consciously considered as complying with corporate environmentalism. In this research, the triangulated data collection approach comprised of document analysis, observation and ten semi-structured interviews with managers and directors of three small and medium manufacturing companies, who had experienced corporate environmentalism associated with stone mining, food production, and automotive component manufacturing. Interview transcripts were synthesized with other qualitative sources of data highlighting experienced corporate environmentalism within the three macro- themes of inner belief and foundation, adaptive dialogue, and cultivating interaction. These three emerged macro- themes later were categorized into nine micro- themes, which offered valuable insight on the executives’ description and their pattern of thinking and cognitive overhead manifested in the executive’s “Neuro-ruling” concerning corporate environmentalism. The results of this study highlighted the gap between the executives’ pattern of thinking in considering environmental sustainability within the confronted mimetic, coercive, and normative isomorphism. These corporate executives appeared to incorporate their perceptual reinforcement (morality, ethics and community) with societal and institutional constraints. Based on the findings, it was concluded that institutional enforcement did not translate into reinforcing the belief and value system, and for these reasons, corporate environmentalism or responsiveness behaviour was generally a fragmented activity and was cut off from the organizational strategic agenda.